Post-traumatic growth and perceived social support in young adolescents during the COVID-19 pandemic - Khadigesadat Kazemi; Hooman Esfahani; Hadis Amiri; Asghar Tavan; Hojjat Farahmandnia (Journal of Emergency Practice and Trauma, 2023)
Objectives: Pandemics would certainly have a negative impact on mental health. Positive modifications as well as negative alterations have been documented in earlier viral pandemic according to previous investigations. Teenagers face a variety of challenges during adolescence. Adolescents may become more concerned if this time coincides with other worries. This study aims to investigate the positive changes that occur in a young adolescent’s life after COVID-19 pandemic, and to see how they relate to perceived social support. Methods: This cross-sectional study was performed on adolescents who were randomly selected from high schools in Kerman, Iran 2020 during the COVID-19. the sample size was 108 and for sampling was used multi-stage random sampling at the end the data was analyzed by Pearson correlation test. Demographic information, the Multidimensional Scale of Perceived Social Support (MSPSS) and Posttraumatic Growth Inventory short form (PTGI-SF) were used to collect data. The data were subjected to descriptive and analytical statistical tests (Pearson correlation) using SPSS software version 24. Results: Statistically a positive correlation was found between the PTG total score and young homeschooled adolescents, parents working remotely, income loss and COVID-19 experience. Moreover, during the COVID-19 pandemic, a positive association was found between perceived social support and PTG total scores in young adolescents. There were also substantial positive connections between the MSPSS subscales and the PTGI overall score. Conclusion: Based on the findings, an overall growth in all areas of PTG was observed during the COVID-19 among young adolescents. Perceived social support scores have a positive and significant relationship with COVID-19 effects. In the crises we face throughout life, intimate family members and friends play a significant supporting role in adapting to these situations.